Pilot study of remote monitoring technologies for frontotemporal lobar degeneration (REMOTE FTLD): Feasibility and compliance: Epidemiology / Innovative methods in epidemiology (i.e., assessment methods, design, recruitment strategies, statistical methods, etc.). (7th December 2020) - Taylor, Jack Carson; Heuer, Hilary W; Vento, Stephanie; Bajorek, Lynn; Ong, Elise; Wang, Ping; You, Michelle; Rosen, Howard J; Staffaroni, Adam M; Boxer, Adam L
Abstract: Background: Familial frontotemporal lobar degeneration (fFTLD) is a group of inherited neurodegenerative diseases that present with alterations in speech and language, motor abilities, cognition, and behavior. Because fFTLD is inherited in an autosomal dominant fashion, asymptomatic participants with mutations can be studied before symptom onset. To date, early detection strategies have focused on data collected in person, usually annually. Although more frequent monitoring would likely improve detection of the earliest clinical manifestations of fFTLD, repeated assessments over shorter intervals would place undue burden on patients and study staff. We evaluated the feasibility and compliance of frequent, remote assessment using a custom smartphone application in participants at risk for or diagnosed with fFTLD. Method: Ten older adults, five functionally intact members of fFTLD kindreds (unknown mutation status), and five symptomatic FTLD participants completed the Revised Self Monitoring Scale and Corticobasal Functional Scale at baseline on their mobile device. They also completed five cognitive tests (e.g., flanker, Stroop, 2‐back) and several speech and language tasks (e.g., picture description) on their mobile phone, three times over the course of ten days. Cognitive pretesting was conducted during the first exposure to the application, and an interview was conducted with participants and study partners at completion. We present qualitative results related to compliance and feasibility. Result: Qualitative analysis of cognitive pretesting interviews suggested that participants generally described their experience as positive. Feedback about specific concerns were used iteratively to improve the user experience. Compliance in the first 10 participants was 97.8%. Post‐study interviews with participants and their caregivers suggested that remote monitoring of cognition, language, and behavior is feasible in this cohort. Conclusion: Early results suggest that a mobile phone application is a feasible methodology for frequent remote data collection in fFTLD. The majority of participants showed high rates of compliance. Future analyses will inform whether this approach can improve early detection and monitoring of people at risk for fFTLD, and allow for symptom tracking in those who are have already developed a clinical syndrome.